The use of municipal solid waste slag as a supplementary cementitious material and the effects of particle size on the properties of slag-derived concrete - Lee, Ming Xue (Nanyang Technological University, 2021)
This project serves to explore the potential of municipal solid waste (MSW) slag as a replacement for sand in concrete mixes as well as a supplementary cementitious material (SCM) for sustainable constructive purposes. The study also looks to investigate how various particle sizes of MSW slag would affect the properties of slag-derived concrete. In total, there are seven design mixes which are tested for compressive strength, leachate performance, X-ray diffraction (XRD), and thermogravimetric analysis (TGA). The control mix with a 1:1 slag-cement ratio demonstrates the highest strength at 60-day (62.2 MPa). The concrete samples produced from slag of varying particle sizes and grinded slag illustrated differing strength developments and eventually achieved strength comparable to the control. Other than satisfactory strength comparisons, the leachate analysis of each mix through water leaching (EN 12457), ion chromatography, and inductively coupled plasma-optical emission spectroscopy indicates acceptable levels of performance according to EN 12457 standards. The XRD and TGA results are also consistent with MSW slag being a potential SCM based on hypothesised pozzolanic behaviour and reinforces the relationship between the strength developmentof different design mixes. Overall, the results suggest potential for utilisation of MSW slag as sand replacement, and possibly as a SCM. The effects of particle size do not really have a pronounced effect on strength and leachate performance based on the analyses. Nevertheless, further studies and investigations would have to be conducted by adjusting various parameters such as design mix and curing age to safely incorporate MSW slag into real-world application and establish a sustainable system.